Development of a functional system for diagnosing the presence of rotor damage in induction traction motors (Transport systems and technologies, 2024)
The aim of this work is to develop a system for functional diagnostics of rotor bar breakage in induction traction motors of railway rolling stock. In order to achieve this aim, the following tasks have been solved: developed an algorithm for diagnosing the condition of rotor bars based on the statistics of fractional moments; developed a block diagram of the unit for diagnosing the condition of rotor bars of the induction motor based on the statistics of fractional moments; developed a block diagram of the system for functional diagnosis of rotor bars condition as part of the traction motor with direct torque control. The most important result consists in obtaining a mathematical model of fractional moment statistics with less volume of calculations and improved sensitivity of the method. This result was achieved by determining the information-frequency range, which made it possible to analyze not all the spectral components of the analyzed signal, but only that part of it where there may be spectralcomponents typical for the breakage of rotor bars of the induction motor. This approach to diagnosing the condition of rotor bars can also be applied in traction motors of rolling stock with vector control system of induction motors.
Keywords: induction motor; fractional moment statistics; rotor bars; direct torque control